2021
DOI: 10.3390/biomedicines9111704
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of BET Inhibition by OTX015 (MK-8628) and JQ1 in NPM1-Mutated (NPM1c) Acute Myeloid Leukemia (AML)

Abstract: BET inhibitors (BETi) including OTX015 (MK-8628) and JQ1 demonstrated antileukemic activity including NPM1c AML cells. Nevertheless, the biological consequences of BETi in NPM1c AML were not fully investigated. Even if of better prognosis AML patients with NPM1c may relapse and treatment remains difficult. Differentiation-based therapy by all trans retinoic acid (ATRA) combined with arsenic trioxide (ATO) demonstrated activity in NPM1c AML. We found that BETi, similar to ATO + ATRA, induced differentiation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Venetoclax alone, or combined to low intensity chemotherapy, Arsenic or menin inhibitors proved efficient in preclinical and more importantly in different categories of NPM1c AML patients including those with minimal residual disease, or relapsed refractory patients [ 29 , 30 , 50 , 51 , 52 , 53 ]. BET-inhibitors also induced differentiation and apoptosis in NPM1c cells following induced proteasome-dependent degradation of NPM1c [ 54 ]. In line with these findings, we demonstrated that EAPB0503, induced the selective growth arrest and apoptosis in NPM1c AML cells following NPM1c proteasomal degradation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Venetoclax alone, or combined to low intensity chemotherapy, Arsenic or menin inhibitors proved efficient in preclinical and more importantly in different categories of NPM1c AML patients including those with minimal residual disease, or relapsed refractory patients [ 29 , 30 , 50 , 51 , 52 , 53 ]. BET-inhibitors also induced differentiation and apoptosis in NPM1c cells following induced proteasome-dependent degradation of NPM1c [ 54 ]. In line with these findings, we demonstrated that EAPB0503, induced the selective growth arrest and apoptosis in NPM1c AML cells following NPM1c proteasomal degradation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results provide a promising epigenetic therapy target for pediatric AML. Other BET inhibitors, including MK-8628 (OTX015) and CPI-0610, also are now being evaluated in phase 1 and 2 trials in adult AML (NCT02698189, NCT02158858) ( 101 ).…”
Section: Epigenetic Targeted Therapy In Pediatric Acute Myeloid Leukemiamentioning
confidence: 99%
“…These results provide a promising epigenetic therapy target for pediatric AML. Other BET inhibitors, including MK-8628 (OTX015) and CPI-0610, also are currently being assessed in phase 1 and 2 trials in adult patients with AML (NCT02698189, NCT02158858) [101].…”
Section: Dot1l Inhibitorsmentioning
confidence: 99%